A hydrazone organic optical modulator with a π electronic system for ultrafast photonics. Issue 34 (5th August 2021) - Zhang, Chenxi; Li, Xiaohui; Wang, Yamin; An, Mingqi; Sun, Zhipeng
Abstract : A ring-type Er-doped fiber laser is designed based on hydrazone compounds with a strongly conjugated π electron structure. We systematically explained the complex spectral sideband in which valley sidebands and peak sidebands coexist. Abstract : Hydrazone organic compounds with a strong conjugation effect have superior characteristics, such as high nonlinear optical sensitivity, short response times, a unique electronic spectrum, and photothermal stability. The conjugated structure of hydrazone compounds leads to its strong dispersion and molecular polarization, and its strong dispersion affects the mutual interference of dispersion wave radiation in a fiber. However, the application of π electron conjugated structures in ultrafast photonics has not been fully studied. Here, nonlinear optical modulation is demonstrated via preparing a set of hydrazone compounds for a mode-locking laser. We applied Hydrazone-1 to an erbium-doped fiber laser, and a 922 fs traditional soliton mode-locked pulse was obtained. Under these conditions, we systematically explained the complex spectral sidebands in which valley sidebands and peak sidebands coexist. Furthermore, a pulse of five bound-state soliton molecules was obtained for the first time. The experiments have proved that hydrazone organic compounds have strong optical properties, which could promote their development as ultrashort pulse light sources upon further research and exploration.